Marine oil dietary supplementation reduces delayed onset muscle soreness after a 30 km run - Baum, K.; Telford, R. D.; Cunningham, R. B. (Open Access Journal of Sports Medicine, 2013)
Runners are prone to delayed onset muscle soreness (DOMS) during long distance training. This especially holds for unaccustomed training volumes at moderate to high intensities. We investigated the effects of a marine oil complex, PCSO-524®, derived from the New Zealand green-lipped mussel (formulated as Lyprinol® and Omega XL®) on DOMS after a 30 km training run. Methods: Initially, peak oxygen uptake of 32 distance runners (4 female, 28 male; median age 45 years, range 28-53) was measured on a treadmill with a 1.5 km hour-1 increase every 4 minutes starting from 8.5 km hour-1. At least 1-week after this initial test, they participated in a 30 km road run at a speed corresponding to about 70% of their individual peak oxygen uptake on a flat terrain. Before and after (0, 24, and 48 hours) the run, blood concentration of creatine kinase (CK) were measured and pain sensation was determined (pain scale from 0 = no pain to 10 = extremely painful). Runners were then matched in pairs based on maximal CK and peak oxygen uptake, and allocated randomly into two different groups. One group was supplemented with 400 mg per day of PCSO-524® for 11 weeks, the other group with an olive oil placebo. After that period, CK and pain sensations were remeasured following a second 30 km run at the same speed and on the same terrain. Results: The general pattern of soreness in the PCSO-524® supplemented group was reduced by 1.1 units (standard error 0.41) compared to the placebo (P < 0.05), the effects being greater in lesser trained runners (P < 0.05). CK levels were positively associated with pain sensation (P < 0.05), but trends toward lower CK in the PCSO-524® group, which were also more pronounced in the lesser trained runners, were not statistically significant. Conclusion: Pain sensations experienced by distance runners following a 30 km run were reduced by supplementation with the marine oil complex PCSO-524®, an effect which was greater in lesser trained runners.